2011
DOI: 10.1143/jjap.50.07hd09
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of Highly Oriented Ta2O5 Piezoelectric Thin Films on Silicon for Fabricating Film Bulk Acoustic Resonator Structure by RF Magnetron Sputtering

Abstract: X -axis-oriented tantalum pentoxide (Ta 2 O 5 ) piezoelectric thin films were deposited on Si using an RF magnetron sputtering system with the aim of obtaining a film bulk acoustic resonator (FBAR) structure. First, the degree of orientation and the coupling factor K 2 for the surface acoustic wave were evaluated. The K 2 of the first mode of the Ta 2 O 5 thin film deposited on the unprocessed Si(100) was almost the same as that of the zeroth mode of the Ta 2 O 5 thin film/SiO 2 glass substrate for a similar t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Piezoelectric thin films with high coupling, high stability, low loss, and high phase velocity are required for the development of high-performance piezoelectric devices, such as surface acoustic wave (SAW) and film bulk acoustic resonator (FBAR) devices. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] An X-axis-oriented Ta 2 O 5 piezoelectric thin film is a relatively new material developed by Nakagawa and coworkers and has a strong piezoelectric property similar to that of ZnO thin films and a high dielectric constant. [16][17][18][19][20][21][22] In the deposition of X-axis-oriented Ta 2 O 5 piezoelectric thin films using an RF magnetron sputtering system with a long-throw sputter (LTS) cathode, Kakio, one of the authors, and colleagues found the optimum deposition conditions for obtaining a strong preferential (200) orientation and a high electromechanical coupling factor K 2 for a Rayleigh-type SAW (R-SAW) on synthetic fused silica (SiO 2 ) glass substrates, 23) and demonstrated the application of the optimum deposition conditions to the fabrication of an FBAR with a Si substrate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Piezoelectric thin films with high coupling, high stability, low loss, and high phase velocity are required for the development of high-performance piezoelectric devices, such as surface acoustic wave (SAW) and film bulk acoustic resonator (FBAR) devices. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] An X-axis-oriented Ta 2 O 5 piezoelectric thin film is a relatively new material developed by Nakagawa and coworkers and has a strong piezoelectric property similar to that of ZnO thin films and a high dielectric constant. [16][17][18][19][20][21][22] In the deposition of X-axis-oriented Ta 2 O 5 piezoelectric thin films using an RF magnetron sputtering system with a long-throw sputter (LTS) cathode, Kakio, one of the authors, and colleagues found the optimum deposition conditions for obtaining a strong preferential (200) orientation and a high electromechanical coupling factor K 2 for a Rayleigh-type SAW (R-SAW) on synthetic fused silica (SiO 2 ) glass substrates, 23) and demonstrated the application of the optimum deposition conditions to the fabrication of an FBAR with a Si substrate.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22] In the deposition of X-axis-oriented Ta 2 O 5 piezoelectric thin films using an RF magnetron sputtering system with a long-throw sputter (LTS) cathode, Kakio, one of the authors, and colleagues found the optimum deposition conditions for obtaining a strong preferential (200) orientation and a high electromechanical coupling factor K 2 for a Rayleigh-type SAW (R-SAW) on synthetic fused silica (SiO 2 ) glass substrates, 23) and demonstrated the application of the optimum deposition conditions to the fabrication of an FBAR with a Si substrate. 1) However, there is a problem in that a large propagation loss for the R-SAW or bulk wave occurs in the oriented Ta 2 O 5 thin films.…”
Section: Introductionmentioning
confidence: 99%
“…24) Moreover, a film bulk acoustic resonator (FBAR) comprising a Ta 2 O 5 thin film and a Si support substrate has been fabricated. 25) However, a large propagation loss (PL) of R-SAWs or BAWs was observed in X-axis-oriented Ta 2 O 5 thin films. The large PL is considered to be due to the crystal grain boundaries inside the thin films.…”
Section: Introductionmentioning
confidence: 99%
“…6) However, optimization of the deposition conditions to reduce the propagation loss and decrease temperature coefficient is required. Similar optimization is also required for an X-axis-oriented Ta 2 O 5 piezoelectric thin film, which can be deposited at a substrate temperature higher than 400 C. [7][8][9][10][11][12][13][14][15] Moreover, the elastic constants of amorphous Ta 2 O 5 thin films have not yet been reported, which are required for the design of SAW devices.…”
Section: Introductionmentioning
confidence: 99%